The Mitogen-Activated Protein Kinase CgMK1 Governs Appressorium Formation, Melanin Synthesis, and Plant Infection of Colletotrichum gloeosporioides - He, Puhuizhong; Wang, Yonglin; Wang, Xiaolian; Zhang, Xiaolin; Tian, Chengming (Frontiers in Microbiology, 2017)
The fungus Colletotrichum gloeosporiodes infects plant hosts with a specialized cell called an appressorium, which is melanized and required for plant cell wall penetration. Here, we show that the mitogen-activated protein kinase CgMK1 governs appressorium formation and virulence in the poplar anthracnose fungus C. gloeosporioides. Deletion of CgMK1 impairs aerial hyphal growth and biomass accumulation, and CgMK1 is responsible for the expression of melanin biosynthesis-associated genes. CgMK1 deletion mutants are unable to form appressorium and lose the capacity to colonize either wounded or unwounded poplar leaves, leading to loss of virulence. We demonstrate that the exogenous application of cAMP fails to restore defective appressorium formation in the CgMK1 deletion mutants, suggesting that CgMK1 may function downstream or independent of a cAMP-dependent signal for appressorium formation. Moreover, CgMK1 mutants were sensitive to high osmosis, indicating that CgMK1 plays an important role in stress response. We conclude that CgMK1 plays a vital role in regulating appressorium formation, melanin biosynthesis, and virulence in C. gloeosporiodes.